Peningkatan Literasi Sains Melalui Pengabdian Masyarakat Berbasis Eksperimen Kimia Sederana di SMAN 30 Garut - Thoriq Thoriq; Rizky Sri Rahayu; Zidhan Firdaus Ramdhani; Ayudya Restu Yudha Pramesthi; Muhammad Yudhistira Azis (Jurnal Pengabdian Masyarakat, 2024)
Scientific literacy is one of the most important aspects in improving the quality of education and human resource development. The level of scientific literacy understanding among students in Indonesia remains comparatively inadequate. Therefore, a chemistry-based community service was conducted at SMAN 30 Garut which aims to improve students' scientific literacy and learning enthusiasm through demonstrations of simple chemical experiments and fun education. This Community Service at SMAN 30 Garut involved members of the HMK “AMISCA” ITB Chemistry Student Association as facilitators in carrying out simple chemical experiments. Several chemical experiments were presented, including the decomposition reaction of hydrogen peroxide, hydrogen balloons, vitamin C testing, secret messages using the Phenolphthalein indicator, and acid-base indicators from colored flower extracts. This activity can improve students' knowledge and interest in science. This is evidenced by the students' enthusiasm in participating in the activities, as well as the results of the feedback distributed after the activities. With the implementation of this chemistry-based community service, it is expected to be a solution in improving scientific literacy and motivating students to further explore the field of science